PENDEKATAN PSIKOTERAPI ISLAM MELALUI SALAT UNTUK MENINGKATKAN KETENANGAN JIWA - Nur Laila Khoirunisa; Heldayanti; Nadya Mahfudzah; Siti Cahaya; Mahfuzi Amin; Arini Safitri (Universitas Muhammadiyah Metro, 2026)
This study aims to describe and analyze the role of salat (Islamic prayer) as an Islamic psychotherapy approach in enhancing the psychological tranquility of students at Madrasah Aliyah Darul Amin Palangka Raya. The study employed a qualitative descriptive method. The participants consisted of five tenth-grade students selected through purposive sampling based on specific criteria, namely students who showed indications of anxiety, emotional distress, restlessness, or difficulties in concentration during learning activities. Data were collected through in-depth interviews, non-participant observation, and documentation. Data analysis was conducted using the Miles, Huberman, and Saldaña model, which includes data reduction, data display, and conclusion drawing. The validity of the data was ensured through source triangulation, technique triangulation, and time triangulation. The findings revealed that salat was perceived to contribute positively to students' psychological tranquility through three main themes. First, salat functions as an emotional regulation mechanism that helps students manage anxiety, restlessness, and psychological pressure. Second, salat serves as a form of spiritual coping that provides inner peace, hope, and strengthens spiritual closeness to Allah SWT when facing various life challenges. Third, the effectiveness of salat in enhancing psychological tranquility is reinforced by social support from family and peers, who serve as important sources of emotional support. The findings indicate that salat is not only understood as a religious obligation but also as a form of Islamic psychotherapy that helps students achieve inner peace and better mental health. Therefore, salat has the potential to be integrated as an approach within Islamic Guidance and Counseling services in schools.